2021
DOI: 10.3390/app11146311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of O2 Addition on the Discharge Parameters and Production of Reactive Species of a Transferred Atmospheric Pressure Plasma Jet

Abstract: The therapeutic effects of atmospheric pressure plasma jets (APPJs) have been associated with the presence of reactive species, mainly the reactive oxygen and nitrogen ones, generated in this kind of plasmas. Due to that, many studies attempting to enhance the production of reactive species in APPJs have been performed. The employment of gas admixtures, usually mixing a noble gas with oxygen (O2) or water vapor, is one of the most common methods to achieve such goal. This work presents a study of how the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In the late 1990s, atmospheric pressure plasma jets (APPJs) appeared to mitigate, reduce or suppress the deficiency mentioned above. APPJs generate plasma plumes in open spaces, enabling the direct treatment of samples of different shapes and sizes [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Over the years, APPJs have been successfully tested in many applications, such as material treatment, sterilization, cancer and wound treatment, aesthetic applications, and dentistry [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s, atmospheric pressure plasma jets (APPJs) appeared to mitigate, reduce or suppress the deficiency mentioned above. APPJs generate plasma plumes in open spaces, enabling the direct treatment of samples of different shapes and sizes [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Over the years, APPJs have been successfully tested in many applications, such as material treatment, sterilization, cancer and wound treatment, aesthetic applications, and dentistry [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…NTAPP is an eco-friendly technology generated by an ionized gas that produces reactive species from the gas phase of plasma, plasma–air interaction, or interaction with treated/activated substrates [ 2 ]. Reactive species are of great scientific interest due to the action of their active constituents in areas such as, medicine, dentistry, agriculture, environment, and food [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The physicochemical reactions generated in plasma interaction with air create reactive species of oxygen and nitrogen (RONS), whose main constituents are nitrates (NO 3 ), nitrite (NO 2 ), peroxynitrite (ONOO − ), hydrogen peroxide (H 2 O 2 ), hydroxyl (OH), oxygen (O 2 ), superoxide (O 2 ), and ozone (O 3 ) [ 2 , 3 , 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most used discharges for PJ generation are dielectric barrier discharge (DBD) and gliding arc (GA) [ 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, the nature of each unloading application may vary slightly within the same area of knowledge; for example, the DBD plasma jet is best suited for wound and tumor treatments [ 22 , 23 , 24 , 25 ] due to lower operating temperature, and does not generate an arc, which can cause a burn on living tissues [ 7 ]. In contrast, for the activation of large volumes of liquids and in the inactivation of fungi, the PJs that generate higher concentrations of RONS are the GA [ 12 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the background outlined above, this Special Issue of Applied Sciences entitled "Frontiers in Atmospheric Pressure Plasma Technology" includes eight original papers [1][2][3][4][5][6][7][8] and two reviews [9,10] providing new insights into the application of atmospheric pressure plasma technology.…”
mentioning
confidence: 99%
“…Furthermore, Nascimento et al [3] revealed the effects of O 2 addition on the discharge parameters and production of reactive species of a transferred atmospheric pressure plasma jet produced at the tip of a long and flexible plastic tube. They concluded that the addition of O 2 to the working gas seems to be useful for increasing the effectiveness of the plasma treatment only when the target modification effect is directly dependent on the content of atomic oxygen.…”
mentioning
confidence: 99%